RAPOR BERKELANJUTAN DALAM SISTEM EVALUASI MULTIDIMENSI: STUDI KASUS INTEGRASI CAPAIAN AKADEMIK DAN PROGRES ATLET PADA KELAS KHUSUS OLAHRAGA - Zacky, Zacky Fanani; Taufiq Hidayat; Junaidi Budi Prihanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Evaluation in Special Sports Classes (KKO) at the elementary school level faces significant challenges in harmonizing national curriculum academic achievements with athletic development progress. This study explores how a multidimensional evaluation system can integrate these two aspects to provide a comprehensive overview of student development. This research employs a qualitative approach with a case study design. Data were collected through in-depth interviews with Physical Education teachers, coaches, and KKO program coordinators at SD Muhammadiyah Surabaya, alongside documentation studies of existing student report models. Data analysis followed the Miles and Huberman model, involving data reduction, data display, and conclusion drawing/verification. Findings reveal a data gap between sports achievements and academic grades within conventional reporting systems. There is an urgent need for an evaluation instrument capable of recording physical and technical parameters periodically (continuously) to support transparency in student progress. Integrating achievements into a single multidimensional evaluation system is proven crucial for facilitating stakeholder communication and maintaining student-athlete motivation. This exploration recommends the reconstruction of KKO report cards into more dynamic and integrated instruments to support the sustainability of early-childhood athlete development within the formal school system.